Pengaruh Model Pembelajaran Inquiry Dan Gaya Kognitif Field Independent (FI) & Field Dependent (FD) Terhadap Hasil Belajar Siswa - Suyuti Suyuti; Sri Yunita Ningsih; Peni Susapti; Muh. Safar; MS. Viktor Purhanudin; Siti Shofiah (Journal on Education, 2023)
This study aims to determine the effect of the inquiry learning model on students' mathematics learning outcomes, the effect of students' cognitive styles on students' mathematics achievement, and the effect of the interaction between the use of learning models and students' cognitive styles on students' mathematics achievement in class VIII (Eight) of SMP Negeri 6 Salatiga for the 2022/2023 academic year. This research was conducted using a quasi-experimental research method by applying a 2 × 2 factorial design. The study population was students of SMP Negeri 6 Salatiga Regency Class VIII even semester of the 2022/2023 academic year. The research sample consisted of 2 experimental classes and 1 control class. Data collection was carried out using two kinds of instruments, namely the Group Embedded Figures Test (GEFT) instrument to measure students' cognitive styles and the instrument to test students' mathematics learning outcomes in the form of essays. The statistical test used is to use a two-way ANOVA to see the effect of learning models and the influence of cognitive style on mathematics achievement as well as the interaction between learning models and students' cognitive styles on students' mathematics achievement. Further testing uses the t test to see differences in student learning outcomes based on students' cognitive styles. The results of data analysis and statistical tests showed that the inquiry learning model had an effect on mathematics achievement, students' cognitive styles had an effect on mathematics learning outcomes, there was no interaction between learning models and cognitive styles on students' mathematics achievement. Based on the results of this research, it is suggested to teachers, especially mathematics teachers, that the application of the inquiry learning model be developed as an innovation in the teaching and learning process.